Optimizing Original Local Government Revenue (PAD) in the Dairi Regency: A Regional Revenue Agency (BAPENDA) Strategy - Wiro Oktavius Ginting; Simson Ginting; Siti Hazzah Nur; Februati Trimurni (Unversitas Muhammadiyah Mataram, 2024)
Abstract: This study aims to increase Regional Original Revenue (PAD) in Dairi Regency and reduce reliance on federal subsidies by improving tax collection and management. The main objective is to evaluate the strategies used by the Dairi Regency Regional Revenue Agency (BAPENDA) to optimize PAD through intensification and extensification of local taxes. Using a descriptive and qualitative approach, the study gathered data through interviews, observations, and document analysis. The findings highlight BAPENDA’s efforts to modernize tax collection, including the implementation of digital payment systems and collaboration with village leaders to extend tax operations. Despite a 15% increase in tax revenue from hotels and restaurants following the introduction of Tapping Boxes, challenges such as staffing shortages and uncollected revenue persist. The study suggests that improving human resources, public awareness, and infrastructure is crucial for long-term success. Future research should assess the socioeconomic impact of PAD optimization on local businesses and services, and explore strategies for sustainable revenue growth.